A Miniaturized 2.4 Ghz Wilkinson Power Divider Using Complementary Split Ring Resonator - Azizuddin, Nur Musyahadah (Universiti Sains Malaysia, 2017)
Wilkinson power dividers (WPD) are an essential element and most popular in the RF and microwave fields. However, a conventional power divider is imperfection as it has a large size because of the 90⁰ branch line which leads to expensive and unmanageable device. Several methods have been proposed to overcome this flaw and the most popular of among these methods is by implementing metamaterial-based resonator. Thus, for this research, complementary split ring resonator (CSRR) is used to miniaturize the WPD while retaining the features. The CSRR is etched on the ground plane. Modelling and designing a conventional WPD and a compact WPD having a wider Bandwidth operate at 2.4 GHz are the main focus of this research. The WPD and CSRR have been designed by using CST Studio Suite software. The design of conventional WPD is exported to CSRR layout to combine for miniaturized WPD. The models are fabricated on Roger RO4003C printed circuit board (PCB) which has a dielectric constant of 3.38 and height of 0.813 mm. Fabricated model is analysed and tested for functionality and performance by using Agilent PNA-X Network Analyser. Scattering parameters (S-parameters) such as reflection coefficient, transmission coefficient and high isolation are considered in this project. Overall, the proposed WPD operates at 4.744 GHz with retun loss of -22.55 dB and almost equal power division of -4.3786 dB, the isolation between the output ports is -29.58 dB and the size reduction is 58.82% smaller than the conventional.